A Usability Evaluation of an E-Commerce Checkout System Using SUS and Usability Testing - Pahlevi, Reynald Daffa; Santoso, Harry Budi (Indonesian Scientific Journal, 2026)
This study focuses on evaluating and improving the usability of the XYZ Checkout System, which previously exhibited several issues that negatively affected transaction completion, including unclear information hierarchy, inconsistent interface behaviour, and inefficient checkout flows. To address these challenges, the research adopted a User-Centered Design (UCD) approach supported by a mixed-method evaluation strategy, combining the System Usability Scale (SUS), usability testing, and open-ended questions. A between-subject research design was employed, involving two independent groups of participants. The initial as-is evaluation was conducted with 35 users and produced an average SUS score of 69.57, indicating marginal usability and the presence of notable interaction barriers. Based on the findings, a high-fidelity to-be prototype was designed using established usability heuristics and UCD principles. The redesigned interface was subsequently evaluated by a different group of 35 users, resulting in a significantly improved average SUS score of 96.64, classified as Excellent with high acceptability. Overall, the results demonstrate that the proposed design improvements successfully enhanced interface consistency, clarity of interaction, and checkout efficiency, emphasizing the critical role of systematic usability evaluation in optimizing e-commerce checkout systems.